Research on Multibeam Pattern Synthesis of Time Modulated Array Based on Convex Optimization. (4th March 2021) - Hu, Jiawen; Dong, Xikuan; Tan, Jing; Jiang, Yachao; Li, Hailin
Abstract : An efficient multibeam pattern synthesis method for time modulated array (TMA) is proposed in this paper. The aim of this method is to generate a beam pattern on the specified sideband of TMA. The pattern synthesis problem is divided into two stages. In the first stage, the sequential convex optimization method is used to suppress the sidelobe of the center frequency and reduce the amplitude dynamic range ratios (DRR). In the second stage, the iterative convex optimization method is used to realize the multibeam pattern synthesis in the sideband. Owing to the introduction of convex optimization, the proposed method could be more efficient than approaches using a global optimization algorithm. The proposed method is capable of realizing pattern synthesis under different DRR constraints and different beam radiation directions. Numerical examples of two beams and four beams patterns of 1000-element time modulated linear array verify the effectiveness of the proposed method.